Preliminary Study of Mechanical Properties of Fiberglass Reinforced Plastic Composites as Materials for Environmentally Friendly Remote Control Lifebuoy - Dwisetiono Dwisetiono; Urip Prayogi; Frengki Mohamad Felayati (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2026)
Safety in waters, whether at sea, in lakes, rivers, or other bodies of water, is crucial. A practical rescue effort is to use a lifebuoy. This research is a preliminary study of Fiberglass Reinforced Plastic (FRP) lifebuoys, which could be an option for remote-controlled, air-pollution-free, electric-powered lifebuoys. The study aimed to obtain data on the mechanical properties of FRP materials with varying numbers of reinforcing layers. Material testing was conducted to determine tensile strength, bending strength, impact strength, and hardness. The results of the study showed that the addition of reinforcing layers to the Fiberglass Reinforced Plastic (FRP) material planned for this remote control lifebuoy material also increased its mechanical properties, namely tensile strength increased by about 20% per layer, bending strength increased by about 15% per layer, shear strength increased by about 28% per layer, and the impact energy absorbed increased by about 50% per additional layer. Meanwhile, the hardness number was not affected by the addition of the number of reinforcing layers.